2017
DOI: 10.1507/endocrj.ej17-0113
|View full text |Cite
|
Sign up to set email alerts
|

Effective waist circumference reduction rate necessary to avoid the development of type 2 diabetes in Japanese men with abdominal obesity

Abstract: The aim of this study was to determine the effective waist circumference (WC) reduction rate in avoiding the development of type 2 diabetes mellitus (T2DM) in <55 years and ≥55 years Japanese men with abdominal obesity. The study subjects were 795 men with WC ≥85 cm, fasting plasma glucose <126 mg/dL, 2-hr plasma glucose on 75 g of oral glucose tolerance test <200 mg/dL, and HbA1c 5.6-6.4 % (38-40 mmol/mol) at baseline who underwent general health checkups more than twice between April 2007 and May 2015. They … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
(21 reference statements)
0
16
0
Order By: Relevance
“…Previous studies have assessed the relationship between abdominal obesity and diabetes incidence [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 33 , 34 ]. Nevertheless, whether the long-term dynamic increase in WC leads to prediabetes is not well described.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have assessed the relationship between abdominal obesity and diabetes incidence [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 33 , 34 ]. Nevertheless, whether the long-term dynamic increase in WC leads to prediabetes is not well described.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to prior longitudinal population-based studies about obesity and diabetes, we found a strong positive association between WC gain and prediabetes. The Suita Study in an urban area of Japan demonstrated that preventing WC gain is important in preventing type 2 diabetes in the Japanese population, especially among participants with a relatively high level of WC [ 28 ]. WC gain can reflect a specific accumulation of visceral adipose tissue, which may cause insulin resistance, contributing to type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations